Construction of Internet of things customer data platform based on OLAP technology - Yue GUO; Yue LONG; Xun ZHANG; Yang QU (物联网学报)
At this stage,the Internet of things (IoT) customer business is developing rapidly.The management problems of weak customer operation ability have gradually exposed in the IoT industry,resulting in the low AP (analytical processing) value of customers,the low profitability and high operating cost.Therefore,it is urgent to enhance the massive data analysis capabilities of the IoT to provide data guidance for business development.To improve the customer value,big data technology,multi-dimensional analysis technology and massive query technology were used to make portraits of IoT enterprise customers,and realize the construction of the customer data platform with refined and efficient operation services.It was introduced how to construct the data operation platform from the aspect of technology implementation.